Key Intermediates: A simple and Highly Selective Synthesis of 5-amino-1-aryl-1H-pyrazole-4-carbonitriles for Applications in the Crop Protection - Plem, Silvana Cristina (2015)
A series of six pyrazoles was synthesized by Michael-type addition reaction. The molecules 5- amino-1-aryl-1H-pyrazole-4-carbonitrile (3a-f) were synthesized from (ethoxymethylene)malononitrile (1) and fluorinated and non-fluorinated aryl hydrazines (2a-f) using ethanol and fluorinated ethanol as solvents at reflux. An excellent regio-selectivity was found when pyrazole derivatives were formed as an exclusive product. No other regioisomer or uncyclised hydrazide was observed. Their structures were confirmed by spectroscopy data (1H, 13C, 19F, COSY (correlation spectroscopy), HSQC (heteronuclear single-quantum correlation spectroscopy) and HMBC (heteronuclear multiple-bond correlation spectroscopy); MS (mass-spectrometry). The yields ranged from good to excellent (47% - 93%) under mild reaction conditions. It would indicate a high selectivity in the one-step work procedure. These products (3a-f) and derivatives have a potential academic and industrial use as key intermediates, in special, for application in crop protection.